2023
DOI: 10.1039/d2ee01588a
|View full text |Cite
|
Sign up to set email alerts
|

Comment on the “Discovery of high-performance thermoelectric copper chalcogenide using modified diffusion-couple high-throughput synthesis and automated histogram analysis technique” by T. Deng, T. Xing, M. K. Brod, Y. Sheng, P. Qiu, I. Veremchuk, Q. Song, T.-R. Wei, J. Yang, G. J. Snyder, Y. Grin, L. Chen and X. Shi, Energy Environ. Sci., 2020, 13, 3041

Abstract: Structural reinvestigations of the Cu7Sn3S10 sample prepared in the reported conditions show that the phase of interest is not tetragonal, but crystallizes in the cubic symmetry. This imposes a re-interpretation of the thermoelectric properties in this system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…As shown in Fig. 2a, the transverse thermopower (S xy ) increases with the increase of the magnetic eld and reaches a peak value of 625 mV K −1 under 14 T at 75 K. This value is much higher compared to previously reported values for another silver chalcogenide, Ag 2 Se, and is comparable to the S xy values of other outstanding transverse thermoelectric materials, [14][15][16][17][18][19][30][31][32][33][34] such as polycrystalline Mg 3+d Bi 2 :Mn x (617 mV K −1 under 14 T at 14 K) and single-crystal NbSb 2 (616 mV K −1 under 9 T at 25 K) (Fig. 2b).…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…As shown in Fig. 2a, the transverse thermopower (S xy ) increases with the increase of the magnetic eld and reaches a peak value of 625 mV K −1 under 14 T at 75 K. This value is much higher compared to previously reported values for another silver chalcogenide, Ag 2 Se, and is comparable to the S xy values of other outstanding transverse thermoelectric materials, [14][15][16][17][18][19][30][31][32][33][34] such as polycrystalline Mg 3+d Bi 2 :Mn x (617 mV K −1 under 14 T at 14 K) and single-crystal NbSb 2 (616 mV K −1 under 9 T at 25 K) (Fig. 2b).…”
Section: Resultssupporting
confidence: 59%
“…For instance, Feng et al reported that polycrystalline Mg 3+d Bi 2 :Mn x exhibits a signicant transverse thermopower of 617 mV K −1 and a power factor of 20 393 mW m −1 K −2 under a 14 T magnetic eld at 14 K. 17 This remarkable performance is attributed to the modulation of chemical pressure through Mn doping, resulting in the transition from a topological insulator to a Dirac semimetal. Li et al revealed that, due to the electron-hole compensation and phonon-drag effect, polycrystalline NbSb 2 achieves a high transverse thermopower of 396 mV K −1 under a 9 T magnetic eld at 21 K. 18 These results indicate that MTE materials are predominantly topological semimetals, characterized by linearly dispersed lowenergy excitations and unique topological surface states. The presence of massless Weyl and Dirac quasiparticles typically results in ultra-high carrier mobility, which is benecial for MTE properties.…”
Section: Introductionmentioning
confidence: 99%
“…The high similitudes in crystal structures and atomic arrangements between them would cause very close results of structure characterization, as those for “Cu 7 Sn 3 S 10 ” 41 and Cu 22 Sn 10 S 32 , 39 of which the former was once identified as a tetragonal phase while being later corrected as a cubic one ( P 4̄3 n ) corresponding to the latter. 42 In this sense, to clarify the detailed phase transformation mechanism in our samples, a further investigation is needed.…”
Section: Resultsmentioning
confidence: 99%
“…Deng et al , further doped with Cl and Br at the S site and achieved zT values of 0.8 and 1, respectively. However, upon further investigation of the crystal structure, Lemoine et al revealed that the stable thermoelectric material discovered by Deng et al was actually Cu 22 Sn 10 S 32 rather than Cu 7 Sn 3 S 10 . Cu 22 Sn 10 S 32 was first reported by Kumar et al In their investigation of the Cu 2+ x Sn 1– x S 3 system, Kumar et al discovered that an intermediate component, Cu 2.075 Sn 0.925 S 3 ( x = 0.075), exhibited a clearly defined pure phase with enhanced thermoelectric properties.…”
Section: Introductionmentioning
confidence: 99%